SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMA BEASISWA BERPRESTASI PADA SMK SNAKMA MUHAMMADIYAH TANJUNG ANOM MENGUNAKAN METODE TOPSIS - Bersama Sinuraya; Rani Novita sari (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2020)
Decision support system (DSS) is a system that can assist someone in making accurate and targeted decisions. Many problems can be solved by using SPK, one of which is that the determination of achievement is an obligation of every child in taking an education so that many things can influence a student to obtain a scholarship from the path of achievement. The best achievement is obtained from several criteria such as attendance, grades , and others. So that a desktop-based decision support system is needed to be more efficient in conducting this assessment so that research is needed from one of the schools in the Deli Serdang area, namely the SMK SNAKMA MUHAMMADYAH TANJUNG ANOM at JL. Snakma No.2 Tanjung Anom, Kec.Pancur Batu. The method in this research is TOPSIS (Technique For Others Reference by Similarity to Ideal Solution). The method in this research utilizes certain techniques, namely by using programming language.